Perancangan Prototype Gerbang Otomatis Berbasis IoT Di Terminal Indihiang Tasikmalaya - Oktavia, Galih Freti; Haryanto, Dadang (Jurnal Media Informatika, 2024)
Indihiang Terminal is an important center for the departure and arrival of public transport, especially inter-city and provincial buses. The traffic and road transport safety inspection process at this terminal is very crucial to ensure passenger safety and comfort. However, currently checking the completeness of documents and recording vehicle identity is still carried out manually, which results in a number of significant problems such as the inspection process which takes time and energy, in the manual process there is a possibility that officers could miss complete documents which should not be ignored, long queues due to slow processes, data management in manual systems is often not well documented, delays in passenger travel due to long queues. To overcome existing problems, a Vehicle Identity Recording Tool (APIK) was designed using IoT-based RFID technology with NodeMCU and integration with Spreadsheets. With this tool, it is hoped that it will be more efficient and effective to improve the safety inspection process at the Indihiang Terminal, as well as being able to reduce the workload of officers, minimize human error, speed up the inspection process, and make it easier to manage inspection result data.